2015
DOI: 10.1530/eje-14-1014
|View full text |Cite
|
Sign up to set email alerts
|

THERAPY OF ENDOCRINE DISEASE: Steroidogenesis enzyme inhibitors in Cushing's syndrome

Abstract: Steroidogenesis enzyme inhibitors are the mainstay of medical therapy in Cushing's syndrome (CS). Ketoconazole (KTZ) and metyrapone are the most commonly used agents. Although there is considerable experience of their use in individual specialist centres, these drugs have not been rigorously tested in prospective clinical trials. Clinicians face uncertainties and concerns with respect to the safety profile of these agents, and best means to monitor effect. We review steroidogenesis inhibitors in the management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
115
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(121 citation statements)
references
References 167 publications
(206 reference statements)
3
115
1
2
Order By: Relevance
“…A review of clinical studies reporting the efficacy of ketoconazole in patients with Cushing's disease revealed a mean response rate of 64.3 % [3]. Ketoconazole, however, also inhibits androgen synthesis and may cause liver damage [61]. The approved agent ketoconazole is a racemic mixture of two enantiomers.…”
Section: Medical Therapymentioning
confidence: 99%
“…A review of clinical studies reporting the efficacy of ketoconazole in patients with Cushing's disease revealed a mean response rate of 64.3 % [3]. Ketoconazole, however, also inhibits androgen synthesis and may cause liver damage [61]. The approved agent ketoconazole is a racemic mixture of two enantiomers.…”
Section: Medical Therapymentioning
confidence: 99%
“…Pituitarydirected approaches include the dopamine agonist cabergoline (18) and the multi-receptor somatostatin-analogue pasireotide (19). Inhibitors of steroidogenesis that inhibit cytochrome P450 enzymes include metyrapone, ketoconazole and LCI699 (20,21). Hypercortisolism can also be controlled by the adrenolytic agent mitotane (22,23,24) and by the glucocorticoid receptor antagonist mifepristone (25).…”
Section: Introductionmentioning
confidence: 99%
“…Ketoconazole inhibits key cytochrome P450 (CYP) enzymes involved in multiple steps of steroidogenesis in the adrenal cortex, including CYP17A1, CYP11A1, CYP11B1, and CYP11B2 [10, 14, 15]. Ketoconazole is a 50/50 racemic mixture of 2S,4R and 2R,4S enantiomers [16], and these enantiomers exhibit differences in inhibitory potency for the enzymes involved in steroidogenesis [1719].…”
Section: Adrenal Steroidogenesis Inhibitors Currently In Clinical Usementioning
confidence: 99%
“…Metyrapone is FDA approved for the diagnosis of AI in the US [27] and is used clinically, off label, for the treatment of CS [10]. In the European Union, metyrapone is approved for the treatment of CS [13].…”
Section: Adrenal Steroidogenesis Inhibitors Currently In Clinical Usementioning
confidence: 99%
See 1 more Smart Citation